Radio Free Banff - '89 days of RADIA 89.9 FM : Artists Catalogue : essays, letters, journal, audio portrait. - The Banff Centre School of Fine Arts, Banff (Banff : The Banff Centre for the Arts Banff, 1989)
Bull, Hank ; Culbert, Jeff ; Fischer, Elizabeth ; Lander, Dan ; Lee, Brent ; Radford, Laurie ; Robertson, Iain ; etc.
Radio Free Banff - '89 days of RADIA 89.9 FM : Artists Catalogue : essays, letters, journal, audio portrait, a radio workshop by Inter-Arts, The Banff Centre for the arts, September 17 - December 14, 1989
boek